A prospective study of erectile dysfunction in men after pelvic surgical procedures and its association with non-modifiable risk factors - Artemi, S.; Vassiliu, Pantelis; Arkadopoulos, Nikolaos F.; Smyrnioti, Maria-Eleni; Sarafis, Pavlos; Smyrniotis, Vassilis (My University, 2019)
Objective: A pelvic surgery can cause erectile dysfunction. The purpose of this study was to evaluate erectile function at various times after pelvic surgery in male patients; to search the non-modifiable risk factors associated with the presence and intensity of sexuality in these patients. This prospective study used the erectile dysfunction IIEF scale. Results: The study population comprised of 106 male patients who had undergone minor pelvic surgery at least 9 months before and during the 2010-2016 period in the 4th Surgical Clinic. A control group of healthy males (N = 106) who underwent no pelvic surgery matched for age was also used for reference values. The main age of the participants was 66.16 ± 13.07 years old. A history of colectomy was present in 36.8%, 18.9% had undergone sigmoidectomy, and 33% inguinal hernia repair. The percentage of severe erectile function increased from 38.7% before surgery to 48.1% (25% increase) after surgery, at the end of the follow-up period (p < 0.05). In the multivariate analysis model, age emerged as an independent predictor of erectile function (p < 0.001). Age was the most important determinant of the IIEF score, which was aggravated by 25% from the first to the last assessment of patients.
Keywords: Erectile dysfunction; Pelvic surgery; Risk factors